Modified water-oxygen barrier film, flexible perovskite battery, and preparation method and application thereof
By introducing a modified water-oxygen barrier film on the edge of the flexible perovskite battery, the bonding reinforcement layer of components such as polyurethane hot melt adhesive increases the interface adhesion between the butyl glue and the water-oxygen barrier film, the problem of water vapor penetration is solved. Extends battery life and improves stability.
Patent Information
- Application Number
- CN202411339177.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The problem of water vapor permeability at the edges of flexible perovskite batteries leads to chemical reactions of materials, affecting battery performance and life. The existing technology is difficult to effectively solve the problem of poor interface bonding between butyl glue and flexible polymer substrate.
The modified water-oxygen barrier film is adopted, including the base water-oxygen barrier material, an adhesive reinforcement layer and a butyl adhesive layer. The adhesive reinforcement layer is composed of polyurethane hot melt adhesive, silane coupling agent, ultraviolet absorber and free radical capture agent. The fastness between the butyl glue and the water-oxygen barrier film is improved by bonding the reinforcement layer, and water vapor penetration is prevented.
It significantly improves the interface bonding between butyl glue and water-oxygen barrier membrane, extends the service life of flexible perovskite batteries, enhances the stability and durability of the batteries, and especially shows long-term work under aging and high temperature conditions. stability.
Smart Images

Figure CN118853011B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible perovskite solar cells, and specifically relates to a modified water-oxygen barrier film, a flexible perovskite cell, and a preparation method and application thereof. Background Art
[0002] As a new type of photovoltaic cell, perovskite cells have the advantages of high efficiency, low cost, and flexibility, but their stability in use remains a key challenge. Packaging can effectively solve the stability problem and extend the service life of the equipment. Reliable packaging technology can achieve excellent airtightness of the package, forming a stable working environment, preventing the intrusion of external water and oxygen, and also blocking the decomposition products of the battery from overflowing from the system. The problem of water vapor permeation at the edge of perovskite cells is a key factor restricting their use. Water vapor permeation can cause chemical reactions in the internal materials of the battery, thereby affecting the performance and life of the battery. The dense arrangement of side methyl groups in the butyl rubber molecular chain limits the thermal motion of the polymer molecules, so it has a lower water vapor permeability and good airtightness. At present, the use of simple, low-cost packaging technology combining polyisobutylene, polyolefin low-temperature adhesive film and glass can improve the durability of glass-based perovskite solar cells.
[0003] Flexible perovskite photovoltaics is a new type of solar cell technology with a wider range of application scenarios, which can meet the needs of different fields for efficient, lightweight and flexible solar power sources. By preparing ultra-light and ultra-thin flexible perovskite devices on micron-scale polymer substrates, it can meet the needs of high efficiency and ultra-lightness, while having outstanding high mass-to-power ratio. However, since polymer substrates mostly use commonly used polymer materials such as PET (polyethylene terephthalate), PEN (polyethylene naphthalate), and PI (polyimide), the substrate itself has poor water vapor barrier properties, which puts higher requirements on the packaging of flexible perovskite batteries. Usually, a material combination of ultra-high water and oxygen barrier film combined with polyolefin film and butyl adhesive is used for device packaging. An ultra-high water and oxygen barrier film is required to ensure the water vapor barrier level of the upper and lower surfaces of the entire battery (<10 -3 g / m 2 / day). Since the film itself has poor water barrier properties (usually > 5g / m 2 / day), which puts forward higher requirements on the water vapor barrier performance of the battery edge. It is required to use high-performance butyl rubber to seal the edge of the component to ensure that the water vapor is blocked outside during the warranty period of the component, and does not penetrate the sealant and enter the battery area.
[0004] The interfacial adhesion between butyl rubber and the flexible polymer substrate is very poor. Under the influence of various aging and external bending forces, interfacial stratification is likely to occur, causing water vapor to quickly penetrate into the battery from the stratified interface, causing battery failure.
[0005] Chinese patent CN118271980A provides a photovoltaic module and its manufacturing method, and a battery module. The photovoltaic module includes: a multilayer film material, at least one layer of the multilayer film material is a micro-crosslinked film with thermosetting properties, and the remaining film materials in the multilayer film material except the micro-crosslinked film are thermoplastic adhesive films. This technical solution can improve the problem of softening and deformation of photovoltaic adhesive films at high temperatures, and can effectively improve the mechanical strength of photovoltaic adhesive films. Therefore, when photovoltaic adhesive films are used in battery modules, the micro-crosslinked film with thermosetting properties can improve the stability of the battery module and improve the problem of mechanical load reduction and backplane detachment of the battery module at high temperatures. However, this solution does not involve the use of butyl adhesive film, and cannot solve the problem of poor interfacial adhesion between butyl adhesive and flexible polymer substrate, which leads to edge water vapor penetration.
[0006] Therefore, how to effectively solve the water vapor penetration at the edge of flexible perovskite cells is a technical problem that needs to be solved urgently. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a packaged flexible perovskite battery and a preparation method thereof, by introducing an adhesion enhancement layer at the edge, improving the fastness between the butyl rubber and the water vapor barrier film substrate, preventing the problem of delamination from the edge of the butyl rubber and the entry of water vapor from the interface after aging, thereby effectively extending the service life of the flexible perovskite battery.
[0008] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:
[0009] In a first aspect, the present invention provides a modified water-oxygen barrier film, comprising a base water-oxygen barrier material, an adhesive enhancement layer and a butyl rubber layer, wherein the adhesive enhancement layer is coated on the surface periphery of the base water-oxygen barrier material, and the base water-oxygen barrier material and the butyl rubber layer are bonded by the adhesive enhancement layer; the thickness of the adhesive enhancement layer is 1-10 μm, and the thickness of the butyl rubber layer is 50-1000 μm;
[0010] The base water-oxygen barrier material is a transparent water-oxygen barrier material or a non-transparent water-oxygen barrier material. The transparent water-oxygen barrier material includes a weather-resistant layer, a coating substrate and a water-oxygen barrier layer. The non-transparent water-oxygen barrier material includes a weather-resistant layer (outer layer), an aluminum foil layer, a polymer substrate and a weather-resistant layer (inner layer).
[0011] The bonding enhancement layer is composed of the following components in parts by weight: 85-97 parts of polyurethane hot melt adhesive, 1-5 parts of silane coupling agent, 1-5 parts of ultraviolet absorber, and 1-5 parts of free radical scavenger;
[0012] Wherein, the viscosity of the polyurethane hot melt adhesive is 3000-30000 mPa·s.
[0013] Preferably, the thickness of the adhesion enhancement layer is 2-5 μm.
[0014] Preferably, in a specific embodiment of the present invention, the bonding enhancement layer is at the outer edge of the surface of the base water and oxygen barrier material, with a width of 5 mm, and the width of the butyl rubber layer is 10-20 mm.
[0015] Preferably, in the transparent water and oxygen barrier material:
[0016] The coating substrate is selected from at least one of polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyethylene, polypropylene, polyimide, and polytetrafluoroethylene, and may be a single layer or a multilayer film layer; the coating substrate has a thickness of 5-500 μm, and more preferably 12-100 μm;
[0017] The water and oxygen barrier layer is an inorganic barrier layer, or a paired layer comprising an inorganic barrier layer or an organic barrier layer;
[0018] The weather-resistant layer is selected from a weather-resistant coating or a weather-resistant film layer; the weather-resistant coating is selected from one or more of fluorine-containing coatings, acrylic coatings, polyester coatings, epoxy coatings and polyurethane coatings; the weather-resistant film layer is a film containing polyvinyl fluoride, polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer or modified polyvinyl chloride.
[0019] Preferably, in the non-transparent water and oxygen barrier material:
[0020] The thickness of the aluminum foil layer is 10-40 μm.
[0021] The polymer substrate is polyethylene terephthalate.
[0022] The weather-resistant layer is selected from a weather-resistant coating or a weather-resistant film layer; the weather-resistant coating is selected from one or more of fluorine-containing coatings, acrylic coatings, polyester coatings, epoxy coatings and polyurethane coatings; the weather-resistant film layer is a film containing at least one of polyvinyl fluoride, polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer and modified polyvinyl chloride. As a specific example, the base water and oxygen barrier material can be prepared by vacuum coating. More preferably, the vacuum coating method is selected from at least one of plasma chemical vapor deposition, magnetron sputtering and atomic layer deposition; the water vapor permeability of the base water and oxygen barrier material is not higher than 5×10 -3 g / m 2 / day (In the present invention, the test conditions are a temperature of 38°C and a humidity of 100%RH, where RH is the abbreviation of Relative Humidity).
[0023] Preferably, the viscosity of the polyurethane hot melt adhesive is 3000-30000 mPa·s.
[0024] Preferably, the silane coupling agent is selected from at least one of vinyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltriisopropoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane and vinyltriacetoxysilane.
[0025] Preferably, the ultraviolet absorber is selected from at least one of hydroxyphenol benzotriazole and hydroxyphenol triazine.
[0026] Preferably, the free radical scavenger is a hindered amine free radical scavenger.
[0027] Preferably, the butyl rubber layer is a butyl rubber tape or is prepared by coating butyl glue, and has a thickness of 40-120 μm. Further preferably, the butyl rubber layer has a thickness of 50-1000 μm.
[0028] As a specific example of the present invention, the width of the butyl rubber layer is 10-20 mm.
[0029] In a second aspect, the present invention provides a method for preparing the above-mentioned water and oxygen barrier film, comprising the following steps:
[0030] (1) coating the outer edge of the surface of the water and oxygen barrier film with a coating liquid prepared from the adhesion enhancement layer, and completely curing it under moisture;
[0031] (2) Apply butyl glue or apply butyl tape on the upper surface of the cured bonding enhancement layer to form a butyl glue layer.
[0032] In a third aspect, the present invention provides the use of the above-mentioned water and oxygen barrier film in encapsulating perovskite batteries.
[0033] Preferably, the perovskite cell is a flexible perovskite cell.
[0034] In a fourth aspect, the present invention provides a flexible perovskite battery, which includes, from top to bottom, a window water and oxygen barrier film, an upper glue film, a flexible perovskite battery cell, a lower glue film, and a bottom water and oxygen barrier film, wherein the window water and oxygen barrier film and the bottom water and oxygen barrier film are the above-mentioned modified water and oxygen barrier films.
[0035] Preferably, the adhesive film is a UV-converting thermoplastic polyolefin adhesive film, which can convert ultraviolet light into visible light and has a thickness of 50-500 μm.
[0036] The term "UV conversion" means converting ultraviolet light into visible light.
[0037] Further preferably, the transmittance of the UV-converting thermoplastic polyolefin film at a wavelength of 380-1100 nm is ≥85%, and the transmittance at a UV band of 280-380 nm is <0.5%.
[0038] Preferably, the lower adhesive film is a thermoplastic polyolefin adhesive film with a thickness of 50-500 μm.
[0039] Further preferably, the light transmittance of the thermoplastic polyolefin film at a wavelength of 380-1100 nm is ≥85%.
[0040] Preferably, the flexible perovskite cell sheet comprises a supporting substrate, a perovskite cell device functional layer and a conductive tape.
[0041] Further preferably, the support substrate is selected from at least one of polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyethylene, polypropylene, and polyimide, and is a single-layer or multi-layer film layer; the support substrate has a thickness of 20-300 μm;
[0042] Further preferably, the functional layer of the perovskite cell device is selected from one of a formal (nip) or a trans structure (pin);
[0043] Further preferably, the conductive tape is a tinned copper tape containing a pressure-sensitive conductive adhesive.
[0044] In a fifth aspect, the present invention provides a method for preparing the above-mentioned flexible perovskite battery, comprising the following steps:
[0045] (1) Lay the adhesive film on the surface of the window water and oxygen barrier film;
[0046] (2) Laying a flexible perovskite cell sheet on the surface of the adhesive film described in step (1);
[0047] (3) Laying a lower adhesive film on the surface of the flexible perovskite solar cell described in step (2);
[0048] (4) Laying a bottom water and oxygen barrier film on the surface of the lower adhesive film described in step (3);
[0049] (5) Laminating the materials laid out in step (4) to obtain the flexible perovskite battery.
[0050] Preferably, in step (5), the lamination conditions are: temperature 105-120°C, pressure 60-90 KPa, and time 10-30 min; further preferably, the lamination conditions are: temperature 115°C, pressure 80 KPa, and time 20 min.
[0051] The beneficial effects of the present invention are:
[0052] (1) The present invention introduces an adhesive enhancement layer between the butyl rubber and the water and oxygen barrier film. At the same time, the adhesive enhancement layer is composed of a specific proportion of polyurethane hot melt adhesive, silane coupling agent, ultraviolet absorber and free radical scavenger, which can achieve better interface bonding between the butyl rubber and the water and oxygen barrier layer during the lamination process, with strong bonding force, simple construction and low cost. In addition, the width of the adhesive enhancement layer is controlled to be smaller than the width of the butyl rubber layer, ensuring that the butyl rubber effectively blocks the edge water vapor from penetrating into the battery, and can also improve the delamination and water permeability problems caused by the low bonding force between the edge of the butyl rubber and the water and oxygen barrier film.
[0053] (2) The present invention uses a specific ratio of polyurethane hot melt adhesive to be compounded with a silane coupling agent, an ultraviolet absorber, and a free radical scavenger, which significantly improves the initial and aged interfacial adhesion, and the material itself has a longer service life, ensuring that the bonding enhancement layer can achieve long-term working stability at low and high temperatures.
[0054] (3) The adhesive film of the present invention adopts UV light-converting adhesive film, which can not only improve the photoelectric conversion efficiency of the flexible perovskite battery, but also effectively improve the ultraviolet radiation stability of the flexible perovskite battery after encapsulation, enhance the water and oxygen barrier and the interface adhesion strength of the entire surface of the perovskite battery cell, and increase the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 It is a schematic structural diagram of the flexible perovskite battery of the present invention;
[0056] In the figure: 1-window water and oxygen barrier film, 2-upper adhesive film, 3-flexible perovskite battery cell, 4-lower adhesive film, 5-bottom water and oxygen barrier film.
[0057] Figure 2 A top view of the edge structure of the modified water and oxygen barrier film of the present invention;
[0058] In the figure: 11-base water and oxygen barrier material, 13-butyl rubber layer.
[0059] Figure 3 is a cross-sectional view of the modified water and oxygen barrier film of the present invention;
[0060] In the figure: 11-base water and oxygen barrier material, 12-adhesion reinforcement layer, 13-butyl rubber layer. DETAILED DESCRIPTION
[0061] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0062] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Unless otherwise specified, the contents described below are all weight contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.
[0063] In the following embodiments:
[0064] The base water and oxygen barrier material size is 35cm×35cm (USA 3M, UBF512).
[0065] Butyl tape WVTR≤3×10 -2 g / m 2 / day (test conditions 38℃, 100RH%).
[0066] UV transfer film, Raybo series thermoplastic POE (polyolefin elastomer), weight 500g / m 2 , film size 320mm×320mm.
[0067] The thermoplastic material of the lower film is TPO (thermoplastic polyolefin elastomer), with a gram weight of 100g / m 2 , film size 320mm×320mm.
[0068] Flexible perovskite cell model SF-01-35×35.
[0069] Polyurethane hot melt adhesive (SUNTIP 2011L) is a liquid reactive single-component polyurethane hot melt adhesive, which is prepared by reaction with a polyol mixture as a soft segment and an excess of diisocyanate as a hard segment. The viscosity is 10000-20000mPa·s (25℃). The hot melt adhesive has excellent bonding strength to substrates such as PET film, and has excellent high temperature and humidity resistance and high high temperature peel strength.
[0070] Example 1
[0071] (1) Apply the coating liquid of the bonding enhancement layer on the outer periphery of the inner surface of the base water and oxygen barrier material (35 cm × 35 cm). The coating liquid formula of the bonding enhancement layer is as follows:
[0072] Polyurethane hot melt adhesive (SUNTIP 2011L) 85%
[0073] Silane coupling agent (vinyl tri(β-methoxyethoxy)silane) 5%
[0074] UV absorber (BASF Tinuvin 479) 5%
[0075] Free radical scavenger (BASF Tinuvin 123) 5%,
[0076] The film was cured at 40 RH% humidity for 60 min and completely cured to obtain an adhesion enhancement layer with a width of 5 mm and a thickness of 5 μm.
[0077] A butyl tape with a width of 10 mm and a thickness of 650 μm was applied on the surface of the bonding enhancement layer to obtain a modified water and oxygen barrier film.
[0078] (2) Take the water and oxygen barrier film as the window transparent water and oxygen barrier film, and lay the adhesive film on the surface (the adhesive film is UV light-transmitting adhesive film, Raybo series), with a gram weight of 500g / m 2 .
[0079] (3) Place a flexible perovskite cell on the surface of the adhesive film.
[0080] (4) Lay the lower adhesive film on the surface of the flexible perovskite battery, with a weight of 100g / m 2 .
[0081] (5) Lay a water and oxygen barrier film on the surface of the lower adhesive film as a bottom water and oxygen barrier film.
[0082] (6) Place the laid materials into a laminator at a laminating temperature of 115°C, a laminating pressure of 80 KPa, and a laminating time of 20 min. After cooling, the flexible perovskite solar cell packaging is completed.
[0083] The structure of the obtained flexible perovskite battery is as follows Figure 1 The flexible perovskite battery comprises, from top to bottom, a window water-oxygen barrier film 1, an upper adhesive film 2, a flexible perovskite battery sheet 3, a lower adhesive film 4, and a bottom water-oxygen barrier film 5, wherein the window water-oxygen barrier film 1 and the bottom water-oxygen barrier film 5 are both modified water-oxygen barrier films, such as Figure 2 As shown, the modified water and oxygen barrier film includes a base water and oxygen barrier material 11, an adhesive reinforcement layer 12 and a butyl rubber layer 13, wherein the adhesive reinforcement layer is coated on the outer surface of the base water and oxygen barrier material, and the base water and oxygen barrier material and the butyl rubber layer are bonded by the adhesive reinforcement layer.
[0084] Example 2
[0085] Different from Example 1, the coating liquid formula of the adhesion enhancement layer is as follows:
[0086] Polyurethane hot melt adhesive (SUNTIP 2011L) 90%
[0087] Silane coupling agent (vinyl tri(β-methoxyethoxy)silane) 4%
[0088] UV absorber (BASF Tinuvin 479) 4%
[0089] Free radical scavenger (BASF Tinuvin 123) 2%,
[0090] The film was cured at 40 RH% humidity for 60 min and completely cured to obtain an adhesion enhancement layer with a width of 5 mm and a thickness of 5 μm.
[0091] The rest is the same as in Example 1.
[0092] Example 3
[0093] Different from Example 2, the coating liquid formula of the adhesion enhancement layer is as follows:
[0094] Polyurethane hot melt adhesive (SUNTIP 2011L) 93%
[0095] Silane coupling agent (vinyl tri(β-methoxyethoxy)silane) 3%
[0096] UV absorber (BASF Tinuvin 479) 3%
[0097] Free radical scavenger (BASF Tinuvin 123) 1%,
[0098] The film was cured at 40 RH% humidity for 60 min and completely cured to obtain an adhesion enhancement layer with a width of 5 mm and a thickness of 5 μm.
[0099] The rest is the same as Example 2.
[0100] Example 4
[0101] Different from Example 2, the coating liquid formula of the adhesion enhancement layer is as follows:
[0102] Polyurethane hot melt adhesive (SUNTIP 2011L) 95%
[0103] Silane coupling agent (vinyl tri(β-methoxyethoxy)silane) 2%
[0104] UV absorber (BASF Tinuvin 479) 1%
[0105] Free radical scavenger (BASF Tinuvin 123) 2%,
[0106] The film was cured at 40 RH% humidity for 60 min and completely cured to obtain an adhesion enhancement layer with a width of 5 mm and a thickness of 5 μm.
[0107] The rest is the same as Example 2.
[0108] Example 5
[0109] Different from Example 2, the coating liquid formula of the adhesion enhancement layer is as follows:
[0110] Polyurethane hot melt adhesive (SUNTIP 2011L) 97%
[0111] Silane coupling agent (vinyl tri(β-methoxyethoxy)silane) 1%
[0112] UV absorber (BASF Tinuvin 479) 1%
[0113] Free radical scavenger (BASF Tinuvin 123) 1%,
[0114] The film was cured at 40 RH% humidity for 60 min and completely cured to obtain an adhesion enhancement layer with a width of 5 mm and a thickness of 5 μm.
[0115] The rest is the same as Example 2.
[0116] Example 6
[0117] The difference from Example 2 is that the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the rest is the same as Example 2.
[0118] Example 7
[0119] The difference from Example 2 is that the silane coupling agent is vinyl triacetoxy silane, and the rest is the same as Example 2.
[0120] Example 8
[0121] The difference from Example 1 is that the silane coupling agent is vinyl triacetoxy silane, and the rest is the same as Example 1.
[0122] Example 9
[0123] The difference from Example 2 is that the ultraviolet absorber is BASF Tinuvin 400, the free radical scavenger is BASF Tinuvin 123, and the rest is the same as Example 2.
[0124] Example 10
[0125] The difference from Example 2 is that the thickness of the bonding enhancement layer is 10 μm, and the rest is the same as Example 2.
[0126] Embodiment 11
[0127] The difference from Example 2 is that the thickness of the bonding enhancement layer is 2 μm, and the rest is the same as Example 2.
[0128] Example 12
[0129] The difference from Example 2 is that the thickness of the bonding enhancement layer is 1 μm, and the rest is the same as Example 2.
[0130] Comparative Example 1
[0131] The difference from Example 2 is that no adhesion enhancement layer is prepared in Comparative Example 1, and the rest is the same as Example 2.
[0132] Comparative Example 2
[0133] The difference from Example 2 is that the adhesive film laid on the surface of the window transparent water and oxygen barrier film is a non-UV light-converting thermoplastic POE adhesive film with a gram weight of 450g / m 2 The film size is 320 mm × 320 mm, and the rest is the same as in Example 2.
[0134] Comparative Example 3
[0135] Different from Example 2, the coating liquid formula of the adhesion enhancement layer is as follows:
[0136] Polyurethane hot melt adhesive (SUNTIP 2011L) 98%
[0137] Silane coupling agent (vinyl tri(β-methoxyethoxy)silane) 1%
[0138] UV absorber (BASF Tinuvin 479) 0.5%
[0139] Free radical scavenger (BASF Tinuvin 123) 0.5%,
[0140] The film was cured at 40 RH% humidity for 60 min and completely cured to obtain an adhesion enhancement layer with a width of 5 mm and a thickness of 5 μm.
[0141] The rest is the same as Example 2.
[0142] Comparative Example 4
[0143] The difference from Example 2 is that the thickness of the bonding enhancement layer is 15 μm, and the rest is the same as Example 2.
[0144] Comparative Example 5
[0145] The difference from Example 2 is that the thickness of the bonding enhancement layer is 0.5 μm, and the rest is the same as Example 2.
[0146] Comparative Example 6
[0147] Different from Example 2, the coating liquid formula of the adhesion enhancement layer is as follows:
[0148] Polyurethane hot melt adhesive (SUNTIP 2011L) 90%
[0149] Silane coupling agent (vinyl tri(β-methoxyethoxy)silane) 4%
[0150] UV absorber (BASF Tinuvin 479) 6%,
[0151] The film was cured at 40 RH% humidity for 60 min and completely cured to obtain an adhesion enhancement layer with a width of 5 mm and a thickness of 5 μm.
[0152] The rest is the same as Example 2.
[0153] Results Test
[0154] The flexible perovskite cells prepared in the above examples and comparative examples were subjected to interlayer adhesion test between butyl rubber and water and oxygen barrier film, photoelectric conversion efficiency test, wet heat test DH1000 (ultra-high stability is required for continuous operation for more than 1000 hours at 85°C and 85%RH) and UV irradiation UV120kWh / m 2 Interlayer adhesion test and photoelectric conversion efficiency test after aging.
[0155] Test method:
[0156] (1) Interlayer adhesion test: According to GB / T 2790-1995, adhesive 180° peel strength test method.
[0157] (2) Photoelectric conversion efficiency test: carried out in accordance with GB / T 34160-2017 "Test method for photoelectric conversion efficiency of terrestrial photovoltaic modules".
[0158] The test results are as follows:
[0159] Table 1.
[0160]
[0161] Table 2.
[0162]
[0163] The results show that the flexible perovskite battery prepared in the embodiment of the present invention has improved adhesion and durability. From the results of the comparative example, it can be seen that the setting of the adhesion enhancement layer, as well as the composition formula and thickness, will have a significant impact on the thickness of the battery. In addition, the selection of a non-light-converting adhesive film for the adhesive film will significantly reduce the photoelectric conversion efficiency.
Claims
1. A flexible perovskite battery, characterized in that: From top to bottom, it includes a window water and oxygen barrier film, an upper adhesive film, a flexible perovskite battery sheet, a lower adhesive film, and a bottom water and oxygen barrier film, wherein the window water and oxygen barrier film and the bottom water and oxygen barrier film are modified water and oxygen barrier films; The adhesive film is a UV-convertible thermoplastic polyolefin adhesive film; The modified water-oxygen barrier film comprises a base water-oxygen barrier material, an adhesive enhancement layer and a butyl rubber layer, wherein the adhesive enhancement layer is coated on the outer surface of the base water-oxygen barrier material, and the base water-oxygen barrier material and the butyl rubber layer are bonded by the adhesive enhancement layer; the thickness of the adhesive enhancement layer is 1-10 μm, and the thickness of the butyl rubber layer is 50-1000 μm; The base water-oxygen barrier material is a transparent water-oxygen barrier material or a non-transparent water-oxygen barrier material, wherein the transparent water-oxygen barrier material comprises a weather-resistant layer, a coating substrate and a water-oxygen barrier layer, and the non-transparent water-oxygen barrier material comprises an outer weather-resistant layer, an aluminum foil layer, a polymer substrate and an inner weather-resistant layer; The bonding enhancement layer is composed of the following components in parts by weight: 85-97 parts of polyurethane hot melt adhesive, 1-5 parts of silane coupling agent, 1-5 parts of ultraviolet absorber, and 1-5 parts of free radical scavenger; The bonding enhancement layer is at the outer edge of the surface of the base water and oxygen barrier material, with a width of 5 mm, and the width of the butyl rubber layer is 10-20 mm.
2. The flexible perovskite battery according to claim 1, characterized in that: The thickness of the bonding enhancement layer is 2-5 μm.
3. The flexible perovskite battery according to claim 1, characterized in that: In the transparent water and oxygen barrier material: The coating substrate is selected from at least one of polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyethylene, polypropylene, polyimide, and polytetrafluoroethylene; the thickness of the coating substrate is 5-500 μm; the water and oxygen barrier layer is an inorganic barrier layer, or a paired layer comprising an inorganic barrier layer or an organic barrier layer; the weather-resistant layer is selected from a weather-resistant coating or a weather-resistant film layer; the weather-resistant coating is selected from one or more of fluorine-containing coatings, acrylic coatings, polyester coatings, epoxy coatings, and polyurethane coatings; the weather-resistant film layer is a film comprising polyvinyl fluoride, polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, or modified polyvinyl chloride; In the non-transparent water and oxygen barrier material: the thickness of the aluminum foil layer is 10-40 μm, the polymer substrate is polyethylene terephthalate; and the weather-resistant layer is selected from a weather-resistant coating or a weather-resistant film layer.
4. The flexible perovskite battery according to claim 1, characterized in that: The viscosity of the polyurethane hot melt adhesive is 3000-30000 mPa·s.
5. The flexible perovskite battery according to claim 1, characterized in that: The silane coupling agent is selected from at least one of vinyl trimethoxy silane, vinyl tri (β-methoxyethoxy) silane, vinyl triisopropoxy silane, vinyl triethoxy silane, γ-methacryloxypropyl trimethoxy silane and vinyl triacetoxy silane; The ultraviolet absorber is selected from at least one of hydroxyphenol benzotriazole and hydroxyphenol triazine; The free radical scavenger is a hindered amine free radical scavenger; The butyl rubber layer is a butyl tape or is prepared by coating butyl glue.
6. The flexible perovskite battery according to claim 1, characterized in that: The thickness of the UV light-converting thermoplastic polyolefin adhesive film is 50-500 μm; the transmittance of the UV light-converting thermoplastic polyolefin adhesive film under the wavelength of 380-1100 nm is ≥85%, and the transmittance in the UV band of 280-380 nm is <0.5%; The lower adhesive film is a thermoplastic polyolefin adhesive film with a thickness of 50-500 μm; the light transmittance of the thermoplastic polyolefin adhesive film under a wavelength of 380-1100 nm is ≥85%; The flexible perovskite cell sheet comprises a supporting substrate, a perovskite cell device functional layer and a conductive tape; Wherein, the support substrate is selected from at least one of polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyethylene, polypropylene, and polyimide; the support substrate has a thickness of 20-300 μm; and the conductive tape is a tinned copper tape containing a pressure-sensitive conductive adhesive.
7. The method for preparing a flexible perovskite battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Lay the adhesive film on the surface of the window water and oxygen barrier film; (2) Laying a flexible perovskite cell sheet on the surface of the adhesive film described in step (1); (3) Laying a lower adhesive film on the surface of the flexible perovskite solar cell described in step (2); (4) Laying a bottom water and oxygen barrier film on the surface of the lower adhesive film described in step (3); (5) Laminating the materials laid out in step (4) to obtain the flexible perovskite battery.
8. The preparation method according to claim 7, characterized in that: The preparation method of the bottom water and oxygen barrier film and the window water and oxygen barrier film comprises the following steps: (1) coating the outer edge of the surface of the water and oxygen barrier film with a coating liquid prepared from the adhesion enhancement layer, and completely curing it under moisture; (2) Apply butyl glue or apply butyl tape on the upper surface of the cured bonding enhancement layer to form a butyl glue layer.
9. Application of a modified water-oxygen barrier film in encapsulating perovskite batteries, characterized in that: The modified water-oxygen barrier film comprises a base water-oxygen barrier material, an adhesive enhancement layer and a butyl rubber layer, wherein the adhesive enhancement layer is coated on the outer surface of the base water-oxygen barrier material, and the base water-oxygen barrier material and the butyl rubber layer are bonded by the adhesive enhancement layer; the thickness of the adhesive enhancement layer is 1-10 μm, and the thickness of the butyl rubber layer is 50-1000 μm; The base water-oxygen barrier material is a transparent water-oxygen barrier material or a non-transparent water-oxygen barrier material, wherein the transparent water-oxygen barrier material comprises a weather-resistant layer, a coating substrate and a water-oxygen barrier layer, and the non-transparent water-oxygen barrier material comprises an outer weather-resistant layer, an aluminum foil layer, a polymer substrate and an inner weather-resistant layer; The bonding enhancement layer is composed of the following components in parts by weight: 85-97 parts of polyurethane hot melt adhesive, 1-5 parts of silane coupling agent, 1-5 parts of ultraviolet absorber, and 1-5 parts of free radical scavenger; The bonding enhancement layer is at the outer edge of the surface of the base water and oxygen barrier material, with a width of 5 mm, and the width of the butyl rubber layer is 10-20 mm.
10. The use according to claim 9, characterized in that: The thickness of the bonding enhancement layer is 2-5 μm.
11. The use according to claim 9, characterized in that: In the transparent water and oxygen barrier material: The coating substrate is selected from at least one of polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyethylene, polypropylene, polyimide, and polytetrafluoroethylene; the thickness of the coating substrate is 5-500 μm; the water and oxygen barrier layer is an inorganic barrier layer, or a paired layer comprising an inorganic barrier layer or an organic barrier layer; the weather-resistant layer is selected from a weather-resistant coating or a weather-resistant film layer; the weather-resistant coating is selected from one or more of fluorine-containing coatings, acrylic coatings, polyester coatings, epoxy coatings, and polyurethane coatings; the weather-resistant film layer is a film comprising polyvinyl fluoride, polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, or modified polyvinyl chloride; In the non-transparent water and oxygen barrier material: the thickness of the aluminum foil layer is 10-40 μm, the polymer substrate is polyethylene terephthalate; and the weather-resistant layer is selected from a weather-resistant coating or a weather-resistant film layer.
12. The use according to claim 9, characterized in that: The viscosity of the polyurethane hot melt adhesive is 3000-30000 mPa·s.
13. The use according to claim 9, characterized in that: The silane coupling agent is selected from at least one of vinyl trimethoxy silane, vinyl tri (β-methoxyethoxy) silane, vinyl triisopropoxy silane, vinyl triethoxy silane, γ-methacryloxypropyl trimethoxy silane and vinyl triacetoxy silane; The ultraviolet absorber is selected from at least one of hydroxyphenol benzotriazole and hydroxyphenol triazine; The free radical scavenger is a hindered amine free radical scavenger; The butyl rubber layer is a butyl tape or is prepared by coating butyl glue.
Citation Information
Patent Citations
Photovoltaic adhesive film, manufacturing method thereof and battery assembly
CN118271980A
Method for producing a lining segment with a thermoplastic barrier layer
CN104884214A
Perovskite solar cell packaging structure and packaging method thereof
CN112510152A